Performance of the International Myeloma Working Group myeloma frailty score among patients 75 and older. Issue 3 (May 2019) - Murillo, Anays; Cronin, Angel M.; Laubach, Jacob P.; Hshieh, Tammy T.; Tanasijevic, Anna M.; Richardson, Paul G.; Driver, Jane A.; Abel, Gregory A.
Abstract: Objectives: We compared the performance of two frailty scoring systems in predicting survival among older patients with multiple myeloma: the International Myeloma Working Group (IMWG) frailty score (which includes age), and the Fried model for frailty (which does not). Methods: From 2015 to 2018, all patients aged 75 years and older presenting at our institution with a diagnosis of multiple myeloma were approached for a frailty screening assessment. We first categorized patients' frailty using the Fried model. Then, using available deficit measures, we reclassified frailty using the IMWG approach. We compared the performance of the IMWG strategy to the Fried model in terms of association with overall survival. Results: Of the 98 (92%) patients who consented to a baseline frailty assessment, we found 57% discordance among frailty classification between the two scoring systems. Using the IMWG strategy, 9% of the cohort was "fit, " 29% "intermediate-fit, " and 62% "frail." Using the Fried model, 29% of the cohort was "robust, " 52% "pre-frail, " and 19% "frail." Frailty category in the Fried model was predictive of overall survival among our cohort, while frailty category in the IMWG strategy was not (log-rank p = 0.04 vs. 0.34). Conclusion: Among our cohort of older patients with myeloma (aged 75 and higher), the Fried model appears to be a better predictor of survival compared to the IMWG strategy. These results suggest that using age as a criterion to identify frailty in older patients with multiple myeloma may limit treatment options for the functionally vigorous.